A study on English idioms of education with reference to the Vietnamese equivalents / Đặng Thu Trang; GVHD: Lê văn Thanh - Đặng, Thu Trang
This study focused on English idioms of education with reference to the Vietnamese equivalents. Through their syntactic and semantic features, we find out the similarities and differences between English idioms of education and Vietnamese ones under the light of contrastive analysis and cross-cultural perspective. Data used for analysis in this study were mainly collected through dictionaries and the internet. Through analysis of forms of idioms of education in English and Vietnamese, it is deduced that idioms are really important in communication. Idioms are used to express ideas in figurative styles. They bring the vividness and richness to the speakers' speeches. This is the reason why the more skillfully a person uses idioms in his conversations, the more effectively he can establish his communicative relationship. The findings of the thesis illustrate some implications for teachers, learners of English and translators from the use of linguistic features of idioms of education in English and focus on the meanings of the English idioms of education and a comparative analysis with Vietnamese ones. Hopefully, the study may help learners, teachers, and translators of English avoid difficulties in realizing and translating English idioms into Vietnamese and vice versa